PERLINDUNGAN HUKUM TERHADAP NASABAH PENYIMPAN DANA (DEPOSAN) DALAM BENTUK DEPOSITO DI BANK - Faradila Khairunisa; Jasman Nazar (JOURNAL OF LAW AND NATION, 2024)
The purpose of legal protection for bank depositors is to shield them against a range of potential dangers associated with money storage activities. Both the Banking Law and the Consumer Protection Law regulate this kind of protection. This study reviews and assesses relevant legislation and regulations using a normative method. The study's findings demonstrate that banks must compensate clients for any losses incurred by their deposits. Due to the security guarantee of the money customers deposit, this legal protection is anticipated to boost customer confidence in banks and lower the likelihood of future losses and issues.